PERSEPSI MAHASISWA TERHADAP PEMBINAAN KEGIATAN PENGENALAN KAMPUS MAHASISWA BARU (PKMB) OLEH PANITIA DI FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI PADANG - LINDA FITRIA (Jurnal Bahana Manajemen Pendidikan, 2016)
The purpose of this research is to know about the founding of students at faculty of aducation state university of Padang. The type of research is descriptive quantity research. The population are 941 students and the sample are 98 students. Sampling technique using probability random sampling technique. The research instrumen was a questionnaire likert scale models that have been tested for validity and reliability. In general, the result of this research is the founding of students at  faculty of aducation state university of Padang is the good category  with an average score of 3,6. So it can be said that the founding of students is good.